SPIRITUAL FACTORS OF RAISING THE INTELLECTUAL CULTURE OF YOUNG PEOPLE - Khujamberdiev Tursunpolat Egamberdievich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, it is based on the fact that our country is becoming more and more deeply integrated into the system of the world community, the aspiration of our people to take a place among the developed nations of the world requires the development of spiritual factors along with economic factors, high innovative technologies. But the development of the above-mentioned factors depends on the growth of human thinking and the strengthening of creative potential. In the process of deepening of social and economic reforms in the period of new development, it was revealed that some backward concepts left over from the past in the social mind, the vices of administrative command, the moods of tyranny are disappearing, or some young people are being influenced by destructive and alien ideas, the lack of ideological immunity, and the increasing urgency of the issue of freedom of thought.